Audit Sistem Informasi: Perbandingan Kinerja Sistem Operasi Windows 7 dan Windows 10 - Widya Natasya; Nezha Febriyan; Zihan Sari; Dinda Firdawati Simamora (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research aims to audit information system performance by comparing two versions of the Windows operating system, namely Windows 7 and Windows 10. The method used includes testing various performance parameters such as boot time, memory usage, disk access speed, power efficiency, system stability, and performance. multitasking. The research results show that Windows 10 has significant performance improvements compared to Windows 7 in various aspects tested, especially in power efficiency and disk access speed.